Children’s Relationship With Their Pet Dogs and OXTR Genotype Predict Child–Pet Interaction in an Experimental Setting - Kertes, Darlene A.; Hall, Nathan; Bhatt, Samarth S. (Frontiers in Psychology, 2018)
Human–animal interaction (HAI) research has increasingly documented the important role of pet dogs in children’s lives. The quality of interaction between children and their pet dogs, however, is likely influenced by individual differences among children as well as their perceived relationship with their pet dog. Ninety-seven children aged 7–12 years and their pet dogs participated in a laboratory protocol during which the child solicited interaction with their dog, from which time petting and gazing were recorded. Children reported on their perceived relationship with the pet dog via interview. Children provided saliva samples, from which a polymorphism in the oxytocin receptor, OXTR rs53576, which has long been implicated in social behavior, was genotyped. The results showed that OXTR genotype and children’s perceived antagonism with the pet dog predicted the amount of petting, but not gazing, between children and their pet dogs. This research adds to the growing body of HAI research by documenting individual differences that may influence children’s interactions with animals, which is key to research related to pet ownership and understanding factors that may impact therapeutic interventions involving HAI.